CAPACITY BUILDING OF POSYANDU CADRES IN EARLY DETECTION OF SPEECH DELAY IN CHILDREN IN SIDOARJO - Henni Endah; Zawawi Zawawi; Andini Dyah Sitawati; Nanang Haryono; Endang Sholihatin (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This community service program aimed to enhance the capacity of Posyandu cadres in the early detection and intervention of speech delay among young children in Wage Village, Taman Subdistrict, Sidoarjo, through the utilization of the interactive digital application Speech Blubs. The implementation method was designed to be participatory and practical, combining classical training sessions, interactive discussions, application usage simulations, and hands-on mentoring at the Posyandu level. The program was conducted in five structured phases: planning, implementation, mentoring, evaluation, and follow-up. A total of 15 Posyandu cadres participated in the entire series of activities. Evaluation was carried out using pre-test and post-test instruments to assess changes in participants’ knowledge and skills. The results indicated an average score improvement of 68%, reflecting the effectiveness of the training approach. In addition to technical competency, the cadres demonstrated increased confidence in operating the application, conducting developmental observations, and engaging parents in the intervention process. This program affirms that integrating technology-based training with family-centered approaches can significantly strengthen community-level early detection services for speech delay. The model presents potential for replication in other regions with similar needs.